The Influence of Sociodemographic Factors and Disease Characteristics on the Medication Adherence among Hypertensive Patients - Fazidah Aguslina Siregar; Asfriyati Asfriyati (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Hypertension is a major global public health concern associated with increased risk of cardiovascular morbidity and mortality. Despite the availability of effective antihypertensive therapy, suboptimal blood pressure control remains prevalent, particularly in low- and middle-income countries. Poor medication adherence is a key contributing factor, often influenced by various sociodemographic and clinical characteristics. This study aimed to assess the level of medication adherence among hypertensive patients and to examine the association between sociodemographic and clinical factors and adherence behavior in an urban Indonesian population. A cross-sectional study was conducted among 153 hypertensive patients attending six public health centers in Medan City, Indonesia, between August and October 2021. Participants were selected using purposive sampling. Medication adherence was assessed using the validated Indonesian version of the Eight-Item Morisky Medication Adherence Scale (MMAS-8). Data on age, education, income, family history, body mass index, comorbidities, and blood pressure were collected through interviews and direct measurements. Bivariate and multivariate logistic regression analyses were performed using SPSS version 24.0 to identify significant predictors of adherence. Among the participants, 52.3% demonstrated high medication adherence, while 47.7% had low adherence. Multivariate analysis revealed that age ≥45 years (RP = 4.29; p = 0.023), low education level (RP = 1.50; p = 0.044), and family history of hypertension (RP = 2.05; p = 0.040) were significantly associated with adherence. Other variables, including income, BMI, and comorbidities, were not significant predictors. Medication adherence among hypertensive patients remains suboptimal. Targeted interventions focusing on older adults, patients with lower education, and family-centered support may enhance adherence and improve hypertension management outcomes. Keywords: Adherence, Education, Hypertension, Risk factors